The Hydroarylation Reaction-Scope and Limitations - Namyslo, Jan C.; Storsberg, Joerg; Klinge, Jens; Gaertner, Christian; Yao, Min-Liang; Ocal, Nuket; Kaufmann, Dieter Eckhard (MDPI, 2010)
The synthetic potential of stereoselective, palladium-catalyzed hydro(het)arylation reactions of bi-, tri- and tetracyclic (hetero)alkenes in the presence of phospines and arsines as highly efficient ligands was studied. The mechanism of this reductive Heck reaction becomes more complex in the case of benzonorbornenes. Hydroarylation of diazabicyclo[2.2.1]heptenes provides a stereoselective access to aryldiaminocyclopentanes. Electron-deficient arylpalladium complexes shift the reaction towards the product of a formal 1,2-hydrazidoarylation reaction of 1,3-cyclopentadiene by a stereoselective C-N cleavage. Due to steric reasons, rigid bicyclo[2.2.2]octenes react slower in hydroarylation reactions than the corresponding bicyclo[2.2.1]heptenes. The more flexible bicyclo[4.2.2]decene system already tends to undergo domino-Heck reactions, even under reductive conditions. When a tetracyclic cis-allylcyclopropane is carbopalladated in the presence of formates, the neighboring cyclopropane ring is attacked in the first reported example of a pi,sigma domino-Heck reaction.
Keywords: homogenous catalysis; palladium; C-C coupling; domino reaction; rearrangement; mechanism; PALLADIUM-CATALYZED REACTIONS; EPIBATIDINE; NORBORNENE; ARYLATION; LIGAND; Biochemistry & Molecular Biology; Chemistry